Find the laplace transfor?

Solve the initial value problems by the Laplace transform method

y" +2y' -3y = 0 y(0) = 1 y'(0) = 1

1 Answer

Relevance
  • kb
    Lv 7
    7 years ago
    Favorite Answer

    Apply L to both sides:

    (s^2 Y(s) - 1s - 1) + 2(s Y(s) - 1) - 3 Y(s) = 0.

    Solve for Y(s):

    (s^2 + 2s - 3) Y(s) = s + 3

    ==> Y(s) = (s + 3)/(s^2 + 2s - 3)

    ..............= (s + 3)/((s + 3)(s - 1))

    ..............= 1/(s - 1).

    Inverting yields y = e^t.

    I hope this helps!

Still have questions? Get your answers by asking now.